The thyroid and breast cancer. Issue 5 (October 2016) - Smyth, Peter P.A.
Abstract : Purpose of review: The female predominance of diseases of the thyroid and breast makes difficult the separation of an expected association with a causal linkage. This review will examine recent reports on associations between thyroid disease and breast cancer, comparing them with previous studies, with a view to elucidating what pointers are available to suggest either a common pathogenesis or novel thyroid-related therapeutic approach, which might arise from this association. Recent findings: Reports on thyroid–breast cancer associations are reviewed under the following headings: breast cancer prevalence in different thyroid disorders and their effect on risk and outcome; the possible role of thyroid autoimmunity, thyroid enlargement, effect of radioactive iodine treatment, role of stable iodine, possible joint antigens sodium iodide transporter and thyroid peroxidase and thyroid–breast cancer coincidence. Summary: Current studies on thyroid and breast cancer associations confirm earlier findings of the lack of definitive evidence of a causal relationship. The predominant relationship continues to be hypothyroidism or autoimmune thyroid disease perhaps contributing to increased breast cancer risk or outcomes. However, despite many studies and the findings of meta-analyses, elucidating the mechanisms underlying the association remains elusive. At present, there is little justification for utilizing thyroid insights as a possible therapeutic intervention in breast cancer.